Kirkebygninger i religionsmodellens grænseflade. Mellem fælles kulturarv og folkekirkeligt magtmonopol - Iversen, Hans (Religionsvidenskabeligt tidsskrift, 2015)
The organization and work of The Danish National Church form the core of the Danish model of religion. One might, therefore, think that this would also include the church buildings used by the church. I argue that the church buildings used by The National Church and especially the pre-Reformation buildings are placed in the borderland of the Danish model of religion, since they belong to the common cultural heritage although they are administered by the church. I analyze the historically conditioned ownership followed by an outline of the interpretations of the buildings endorsed by respectively the official church and its members. The special situation pertinent to the church buildings of Copenhagen is described before the final analysis of the principles underlying the decision by the Minister of Cultural Affairs on the bishop's suggestion to close down 14 churches in Copenhagen in 2013. I conclude that church buildings in Denmark hold a status similar to holy cows in India.